1987
DOI: 10.1007/bf00533393
|View full text |Cite
|
Sign up to set email alerts
|

Immunological characterization of chromogranins A and B and secretogranin II in the bovine pancreatic islet

Abstract: Summary. Antisera against chromogranin A and B and secretogranin II were used for analysing the bovine pancreas by immunoblotting and irnmunohistochemistry. All three antigens were found in extracts of fetal pancreas by one dimensional immunoblotting. A comparison with the soluble proteins of chromaffin granules revealed that in adrenal medulla and in pancreas antigens which migrated identically in electrophoresis were present. In immunohistochemistry, chromogranin A was found in all pancreatic endocrine cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Many authors conclude that the best diluent buffer for MAbs and PAbs is 0.05 to 0.1 M Tris buffer (pH 6.0), but there are exceptions. 31,33,429 Tris buffer should also be used for alkaline phosphatase procedures, because the high concentration of inorganic phosphate competes for the phosphatase. 89 Background reactivity due to ionic interactions can be reduced by increasing the NaCl concentration in the buffer to 0.3 to 0.5 M; 277 however, increased ionic strength can disrupt the binding of specific but low-affinity antibodies, so it should be used judiciously.…”
Section: Diluent Buffermentioning
confidence: 99%
“…Many authors conclude that the best diluent buffer for MAbs and PAbs is 0.05 to 0.1 M Tris buffer (pH 6.0), but there are exceptions. 31,33,429 Tris buffer should also be used for alkaline phosphatase procedures, because the high concentration of inorganic phosphate competes for the phosphatase. 89 Background reactivity due to ionic interactions can be reduced by increasing the NaCl concentration in the buffer to 0.3 to 0.5 M; 277 however, increased ionic strength can disrupt the binding of specific but low-affinity antibodies, so it should be used judiciously.…”
Section: Diluent Buffermentioning
confidence: 99%
“…Cohn et al, 1984;Wilson and Lloyd, 1984;O'Connor, 1983). lmmunohistochemical studies of bovine endocrine pancreas have demonstrated that chromogranin A is present in cells producing insulin (B-cells), glucagon (A-cells), and somatostatin (D-cells) and in a few cells containing pancreatic polypeptide (PP-cells) (Yoshie et al, 1987;Ehrhart et al, 1986). Chromogranin A is co-stored in the same secretory granules as the established hormones (Ehrhart et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a n identical protein was subsequently demonstrated in adrenal medullary chromaffin cells (2). In fact like other members of the chromogranin family, SgII has a widespread distribution, being present in the matrix of secretory granules of a variety of endocrine and neuronal cells including pituitary (I), pancreatic islets (25) and endocrine cells of the gut (26). In neuronal tissue, SgII has been identified in the hippocampus (3), the cerebellum (6) and the splenic nerve (27).…”
Section: Discussionmentioning
confidence: 99%